Problems, Coping, and Efficacy: An Exploration of Subjective Distress in Orphans Placed in Ghanaian Orphanages. - Salifu Yendork, Joana; Somhlaba, Nceba Z. (Journal of Loss & Trauma)
We used the Kidcope scale to explore problems experienced by participants within the preceding month, coping, and coping efficacy for 89 orphaned children sampled from orphanages and 100 nonorphans sampled from public schools in Accra, Ghana. Results revealed that orphaned children reported significantly more relationship problems with peers than nonorphans, whereas for nonorphans problems cited were relationship difficulties with caregivers. With all children considered, resignation featured predominantly to manage problems with caregivers rather than in managing problems with both school and peers. Moreover, adolescents used self-criticism and wishful thinking significantly more than children. Implications of the findings are discussed.